The association between the systemic immune-inflammation index and in-hospital mortality among acute ischemic stroke with atrial fibrillation patients undergoing intravenous thrombolysis - Aierken, Kadiyan; Ma, Liang; Zhu, Yu; Jin, Xinyang; Zhu, Yajie; Zhou, Jiahui; Gao, Jing; Zhao, Hongling; Wang, Tao; Li, Shijun (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study aimed to explore the relationship between the systemic immune-inflammatory index (SII) and the probability of in-hospital mortality among acute ischemic stroke (AIS) with atrial fibrillation (AF) patients undergoing intravenous thrombolysis.MethodsThis single-center, retrospective observational study included individuals among AIS with AF who received intravenous thrombolysis. The SII is determined by taking the product of the platelet and neutrophil counts, followed by dividing this result by the lymphocyte count. In-hospital mortality was defined as a Modified Rankin Scale (mRS) score of 6 point. The investigation applied logistic regression models, along with subgroup, sensitivity, and receiver operating characteristic (ROC) curve analyses assessments, to explore the relationship between the SII and in-hospital mortality.Results541 patients were included in this study, 50 (9.24%) of whom died during their hospital stay. Multifactorial logistic regression analyses using fully adjusted models, demonstrated that the SII is independently associated with the risk of in-hospital death. Patients with elevated SII levels experienced a significantly increased risk of in-hospital mortality, which was found to be 2.557 (95% CI: 1.154–5.665, P = 0.021) times greater compared to those with lower SII levels. Through multivariate logistic regression analyses, a notable correlation between the SII and the probability of death during hospitalization was observed across various subgroups, including individuals aged ≤75 and >75years, women, patients with persistent AF, those receiving thrombolytic therapy, diabetic and nondiabetic patients, individuals with BMI ≥24 kg/m2, and those with an admission National Institutes of Health Stroke Scale score ≤20 (P < 0.05). Two sensitivity analyses confirmed the robustness of this association from multiple perspectives (P < 0.05). ROC analysis demonstrated that the SII, the baseline model, and their combined model all showed strong predictive power for in-hospital mortality. Notably, the combined model outperformed the SII alone (P < 0.05). In addition, the predictive value of SII for in-hospital death was significantly higher than that of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR).ConclusionA significant association has been observed between the risk of in-hospital death among AIS with AF individual undergoing intravenous thrombolysis and the SII.